P087: Pilot project: Implementation of a peer support network for geographically distributed learners in the NOSM family medicine/emergency medicine residency program. (May 2019) - Lyon, T.; Ohle, R.
Abstract : Innovation Concept : Residents bear an enormous burden of responsibility for patient care which can lead to stress and mental exhaustion, especially in the face-paced and acute environment of emergency medicine (EM). In addition to numerous demands faced by EM residents, being a member of a geographically distributive residency program presents many unique challenges from a support and wellness perspective. To address these issues we sought to implement a video conferenced peer support network in hopes to foster wellness in the NOSM Family Medicine/EM program, where learners are commonly separated for training.Methods : Participants completed a pre-pilot questionnaire that strongly showed interest for this type of novel network. Furthermore residents conveyed that they are reluctant to access formal services and commonly rely on co-residents for support. This pilot program intends to decrease barriers that geography and stigma create that negatively hinder seeking support throughout medical training. Keeping the network small, consisting of only co-residents maintains a collegial and confidential environment that enables colleagues to provide relevant help to one another. Offering this outlet allows the opportunity to debrief and share unique experiences, which can lead to improved knowledge and wellbeing.Curriculum, Tool or Material : Informal, co-resident run and easy to access sessions are held twice monthly and average one hour in length. Discussion topics commonly include residency issues, difficult patient encounters and challenging situations. These sessions are conducted via video conferencing making them easily accessible from a distance and also from a comfortable and convenient environment of the participants choosing. Residents have commented that this is a helpful platform to discuss important issues while providing and safe and confidential resource to help cope with residency challenges.Conclusion : Further data analysis is underway as we are in the initial stages of implementing the program. In the final stages (April 2018) a pending post-pilot questionnaire will be interpreted to explore barriers, limitations and to determine the role of the network going forward. If found to be effective it is something that can be implemented and adapted for future residents. Other programs can use this feasible model to increase wellness and foster the same supportive environment among residents, especially those separated geographically from peers who may benefit most.